Refractory Hypotension after Liver Allograft Reperfusion: A Case of Dynamic Left Ventricular Outflow Tract Obstruction - Essandoh, Michael; Otey, Andrew Joseph; Dalia, Adam; Dewhirst, Elisabeth; Springer, Andrew; Henry, Mitchell (Frontiers in Medicine, 2016)
Abstract Hypotension after reperfusion is a common occurrence during liver transplantation following the systemic release of cold, hyperkalemic, and acidic contents of the liver allograft. Moreover, the release of vasoactive metabolites such as inflammatory cytokines and free radicals from the liver and mesentery, compounded by the hepatic uptake of blood, may also cause a decrement in systemic perfusion pressures. Thus, the postreperfusion syndrome can materialize if hypotension and fibrinolysis occur concomitantly within five minutes of reperfusion. Treatment of the postreperfusion syndrome requires the administration of inotropes, vasopressors, and intravenous fluids to maintain hemodynamic stability. However, the occurrence of the postreperfusion syndrome and its treatment with inotropes and calcium chloride, may lead to dynamic left ventricular outflow tract obstruction, precipitating refractory hypotension. Expedient diagnosis of dynamic left ventricular outflow tract obstruction with transesophageal echocardiography is extremely vital in order to avoid potential cardiovascular collapse during this critical period.